Faktor Individu dalam Pelaksanaan Patient Safety oleh Perawat di Ruang Rawat Inap RS X Rengat - Novita Kusumarini; Almahdy Almahdy; Syafrida Syafrida (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Patient safety incidents still found in various regions in Indonesia. ILO, Phlebitis and fall are the common cases found in hospital setting. Nurses play a vital role in patient safety because the nurse is a health worker who is 24 hours with the patient. This study aims to identify the association between individual factors with the implementation of patient safety by nurses in hospital. The design of this study was cross sectional. Data were analyzed using Chi square. Sample of this study were 57 nurses from one public hospital in Rengat. The sample technique used was total sampling. The result showed that there were correlation between knowledge with the implementation of patient safety (p